Rootstock impacts on ‘USDA-ARS-Pawnee’ pecan growth, physiological traits, and soil microbial communities - Wang, Xinwang; Kubenka, Keith; Chatwin, Warren; Hilton, Angelyn; Tondre, Braden; Xu, Tingying; Zhang, Lu (Frontiers in Horticulture, 2025)
IntroductionPecan (Carya illinoinensis), native to North America, is the most commercially significant species within the Carya genus, playing a vital role in nut production across the southern United States. Cultivated for its high-quality nuts, pecans are widely utilized in culinary applications, and their increasing global demand underscores the necessity for enhanced cultivation practices that ensure both economic sustainability and long-term viability. One critical factor influencing pecan production is rootstock selection, which affects growth, physiology, and overall orchard performance. This study investigates the impact of 12 different rootstocks on the growth and physiological characteristics of the ‘USDA-ARS-Pawnee’ scion to provide insights into optimal rootstock choices for pecan orchards.MethodsThe study was conducted over multiple years, assessing key traits including budbreak timing, tree morphology, leaf size, leaf retention, photosynthesis, leaf nutrient composition, and soil microbial community structure. Twelve distinct rootstocks were evaluated to determine their influence on scion development. Measurements of photosynthesis rate (PSR) and water use efficiency (WUE) were collected to establish correlations with leaf size. Leaf nutrient content and soil microbial diversity were analyzed to assess rootstock effects on tree health and orchard sustainability.ResultsSignificant differences in budbreak timing were observed among the rootstocks, with northern rootstocks, particularly ‘Peruque,’ exhibiting the latest budbreak, while eastern rootstocks demonstrated the earliest budbreak. Growth performance varied across rootstock origins; southern (Mexican) rootstocks produced the tallest trees with the largest trunk diameters and canopy widths, highlighting their potential for enhancing orchard productivity. Leaf size differed among rootstocks, with northern and eastern rootstocks generally producing larger leaves, although statistical significance was not established. Larger leaves correlated positively with increased PSR and WUE, with ‘Giles’ (northern) and ‘VC1-68’ (western) exhibiting the highest values, while ‘Elliott’ (eastern) recorded the lowest. Leaf retention showed no significant differences, but northern and eastern rootstocks retained more foliage into early November than southern and western rootstocks. Nutrient analysis revealed rootstock-dependent variations, with ‘Riverside’ containing the highest Zn levels and ‘Peruque’ the lowest, while ‘Major’ exhibited the highest B content, and ‘Frutoso’ the lowest. Soil microbial analysis identified distinct microbial compositions influenced by rootstock selection, with ‘Peruque’ fostering ectomycorrhizal fungi and ‘87MX5-1.7’ supporting nitrogen-fixing bacteria, suggesting rootstock effects on soil microbial diversity and nutrient cycling.DiscussionThese findings highlight the importance of rootstock selection in optimizing pecan tree growth, physiological performance, and soil health. The superior growth of southern rootstocks suggests their potential for improving orchard productivity, while variations in PSR and WUE underscore the complex interactions between rootstocks and photosynthetic efficiency. Additionally, the microbial differences observed indicate that rootstock selection may influence soil nutrient dynamics, further emphasizing the role of rootstocks in sustainable pecan cultivation. Overall, this study provides valuable insights into rootstock-specific advantages, aiding growers in selecting the most suitable rootstocks to enhance pecan orchard management.